Teacher's Efforts To Develop Children's Language Abilities Through Storytelling Method In Paud An-Nur Lebong District - Saleha, Nissrina Nuha; Nirwana, Evi Selva; Andani, Fidhia (International Journal of Education, Information Technology, and Others, 2025)
This study aims to understand teachers' efforts in developing early childhood language skills through the storytelling method at PAUD An-Nur in Lebong Regency. Children aged 5–6 years at this institution exhibit limited language development, such as the inability to narrate stories coherently and low participation in storytelling activities. This research employs a qualitative approach with field research methods. Data were collected through observation, interviews, and documentation involving teachers and early childhood students as the main subjects. The findings show that storytelling is used by teachers to stimulate children's interest in speaking, enrich vocabulary, introduce sentence structures, improve language comprehension, and train storytelling abilities. Despite challenges such as differences in mother tongue backgrounds and low self-confidence among children, teachers manage to overcome these obstacles by creating a supportive learning environment, employing creative teaching strategies, and involving parental support. The storytelling method has proven effective in enhancing children's language abilities